Solving urban infrastructure problems using smart city technologies: Handbook on planning, design, development, and regulation - Edited by Vacca, John R. (Amsterdam Elsevir, 2021)
Solving Urban Infrastructure Problems Using Smart City Technologies is the most complete guide for integrating next generation smart city technologies into the very foundation of urban areas worldwide, showing how to make urban areas more efficient, more sustainable, and safer. Smart cities are complex systems of systems that encompass all aspects of modern urban life. A key component of their success is creating an ecosystem of smart infrastructures that can work together to enable dynamic, real-time interactions between urban subsystems such as transportation, energy, healthcare, housing, food, entertainment, work, social interactions, and governance. Solving Urban Infrastructure Problems Using Smart City Technologies is a complete reference for building a holistic, system-level perspective on smart and sustainable cities, leveraging big data analytics and strategies for planning, zoning, and public policy. It offers in-depth coverage and practical solutions for how smart cities can utilize resident$1 (Bs intellectual and social capital, press environmental sustainability, increase personalization, mobility, and higher quality of life.s
Keywords: Infrastructure Sector; Infrastructure Technology; Urban Infrastructure